IKLIM KOMUNIKASI TOXIC PARENTING (Studi Kasus Pada Pengguna Twitter yang Menjadi Korban Toxic Parenting di Indonesia): Studi Kasus Pada Pengguna Twitter yang Menjadi Korban Toxic Parenting di Indonesia - Nisrina Fadhilah, Rona; Hindra H, Nurnawati; Sarungu, Lukas M (Solidaritas, 2024)
Family communication is communication that occurs in the family environment,which is a way for a family member to interact with other members, and also as a placeto build and develop moral values needed as a guide to life. What happens if a familycommunication and toxic parenting behavior blend in a family will certainly affect childdevelopment. Poor mental health in childhood can cause disruption more seriousbehavior due to mental and emotional imbalances, as well as poor social life of children.The formulation of the problem in this study is to determine the climate ofcommunication in families who apply toxic parenting, and find out how the process ofself-disclosure by victims is carried out through twitter. This study used qualitativedescriptive type. The subjects of this study were victims of toxic parenting. The techniqueof determining informants is using purposive sampling techniques. Techniques in datacollection use literature studies and use triangulation techniques. Data analysistechniques using the miles and huberman interaction model, namely data reduction,drawing conclusions.The results showed that the communication climate in a family environment thatapplies toxic parenting affects mental development and character building in children.The types of violence that occur are physical violence and verbal violence.Keywords : Communication Climate, Toxic Parenting, Family Parenting